Sustainable Midwifery Care (Continuity Of Care) In The Preconception Period in The Working Area Of The Pagambiran Health Center Padang City - Yulizawati, Yulizawati; Aprila, Prety Zinta; Intasir, M. Pemberdi (Universitas Andalas, 2024)
Background: Based on World Health Organization (WHO) data in 2021 that Maternal Mortality Rate (MMR) in the world caused by complications pregnancy and childbirth reached 295,000 (810 per day) people. Meanwhile, The maternal mortality rate in Indonesia recorded in the Indonesian health profile in 2021 is 7,389 mothers in West Sumatra Province. The maternal mortality rate also increased from 125 people in 2020 to 193 people in 2021. This phenomenon is not in accordance with Indonesia's Sustainable Development Goals (SDGs), which states that the maternal mortality rate target is a maximum of 70 deaths per 100,000 live births by 2030. So, the implementation of midwifery Continuity of Care (CoC) is very important as promotional and preventive step to prevent mother complication during pregnancy. Purpose: Providing CoC midwifery care to women during the preconception period. Methods: Implementation of midwifery care in a continuity of care manner with assessment according to midwifery science aims to help women solve the problems they face, with various steps consisting of basic data assessment, data interpretation, potential diagnosis, immediate action, drawing up a comprehensive care plan, implementation, and evaluation, as well as recording through SOAP documentation. S (Subjective) O (Objective) A (Assessment) P(Planning). Results: The condition of the 4 clients was obtained with 2 clients, namely Mrs.V 29 years old with a history of 1 eracs and 1 abortion and Mrs. child and wants to get it back. Apart from that, 2 other clients, namely Mrs.C, 28 years old and Mrs.A, 29 years old, have not been successful in getting pregnant till date. Increasing client knowledge in the form of material discussed with interactive discussions using posters, leaflets and educational videos. Conclusion: Regulation of Health Ministry of Indonesia (PMK 21 of 2021) has regulated the implementation of CoC which aims to reduce morbidity and mortality rates for mothers and newborns. Keywords: midwifery, continuity of care, maternal mortality rate.